1997
DOI: 10.1111/j.1469-7793.1997.031bi.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cutaneous C Fibre Type and Antidromic Vasodilatation in the Rabbit and the Rat

Abstract: Skin blood flow was monitored during antidromic stimulation of identified cutaneous C fibres in fine filaments dissected from the saphenous nerve of anaesthetized rabbits and rats. The techniques used to monitor skin blood flow were laser Doppler perfusion imaging and laser Doppler flowmetry. In the rabbit filaments a total of thirty‐three C fibres were tested for their ability to produce antidromic vasodilatation. The only C fibres found to have vasodilator actions were of the polymodal nociceptor afferent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Axon reflex elicited by nociceptive stimulation may be closely related to the increased release of CGRP from nerve endings. It has been suggested that the axon reflex in human skin is a response neurally mediated by C-fiber nociceptors, which have been shown to stimulate vasodilatation via the release of CGRP and substance P (23). The present results suggested that axon reflex-mediated CGRP release may be a key event involved in facilitation in tumor-associated angiogenesis.…”
Section: Effects Of Continuous Infusion Of a Cgrp Antagonist On Tumorsupporting
confidence: 48%
“…Axon reflex elicited by nociceptive stimulation may be closely related to the increased release of CGRP from nerve endings. It has been suggested that the axon reflex in human skin is a response neurally mediated by C-fiber nociceptors, which have been shown to stimulate vasodilatation via the release of CGRP and substance P (23). The present results suggested that axon reflex-mediated CGRP release may be a key event involved in facilitation in tumor-associated angiogenesis.…”
Section: Effects Of Continuous Infusion Of a Cgrp Antagonist On Tumorsupporting
confidence: 48%
“…For example, silent nociceptors are by far more abundant in man and pig than in rodents (Lynn and Carpenter, 1982;Handwerker et al, 1991;Lynn et al, 1995;Schmidt et al, 1995;Gee et al, 1997). For example, silent nociceptors are by far more abundant in man and pig than in rodents (Lynn and Carpenter, 1982;Handwerker et al, 1991;Lynn et al, 1995;Schmidt et al, 1995;Gee et al, 1997).…”
Section: Pig As a Man-like Animal Model For Nociceptionmentioning
confidence: 99%
“…There is evidence that silent nociceptors are more abundant in human (Schmidt et al, 1995), monkey (Meyer et al, 1991), and pig (Lynn et al, 1995), than in rodents (Lynn and Carpenter, 1982;Handwerker et al, 1991;Gee et al, 1997). Moreover, it has been shown that the axon-reflex induced vasodilatation in skin is mediated by silent nociceptors in both man (Schmelz et al, 2000) and pig Sann and Pierau, 1998), but not in rodents (Gee et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical thresholds, however, remained either unchanged (Andrew and Greenspan, 1999) or decreased upon constant suprathreshold (250 mN) mechanical stimulation (Du et al, 2006). In contrast to rodents (Gee et al, 1997), the sensitization of polymodal nociceptors alone would not entirely explain the generation of an axon reflex erythema recorded in the pig. It may be additionally hypothesized that in UV-B irradiated skin polymodal nociceptors also gain the ability to induce an axon reflex.…”
Section: Mechanical Sensitizationmentioning
confidence: 81%